A CaAl2Si2-Type Magnetic Semiconductor (Sr, Na)(Zn, Mn)2Sb2 Isostructural to 122-Type Iron-Based Superconductors. (10th January 2022) - Gu, Yilun; Zhang, Rufei; Zhang, Haojie; Fu, Licheng; Zhi, Guoxiang; Dong, Jinou; Zhao, Xueqin; Xie, Lingfeng; Ning, Fanlong
Abstract : A new diluted magnetic semiconductor (Sr, Na)(Zn, Mn)2 Sb2 has been successfully synthesized by doping Na and Mn into the parent compound SrZn 2 Sb 2, which has a CaAl 2 Si 2 -type crystal structure (space group P 3 ¯ m 1, No. 164, h P 5 ) isostructural to the 122-type iron-based superconductor CaFe 2 As 2 . No magnetic ordering has been observed when only spins are doped by (Zn, Mn) substitution. Only with carriers codoped by (Sr, Na) substitution, a ferromagnetic ordering occurs below the maximum Curie temperature T C ∼9.5 K. Comparing with other CaAl 2 Si 2 -type diluted magnetic semiconductors, we will show that negative chemical pressure suppresses the Curie temperature.